Introduction to Islamic finance - Zul Kepli, Mohd Yazid (CLJ Publication, 2015)
Introduction to Islamic Finance is a quick and easy guide to Islamic banking and finance, covering both theory and practical aspects in a concise style suitable for bankers, practitioners, university students and any reader new to the topic.